2011
DOI: 10.1128/mcb.05402-11
|View full text |Cite
|
Sign up to set email alerts
|

Importin α-Mediated Nuclear Import of Cytoplasmic Poly(A) Binding Protein Occurs as a Direct Consequence of Cytoplasmic mRNA Depletion

Abstract: Recent studies have found the cytoplasmic poly(A) binding protein (PABPC) to have opposing effects on gene expression when concentrated in the cytoplasm versus in the nucleus. PABPC is predominantly cytoplasmic at steady state, where it enhances protein synthesis through simultaneous interactions with mRNA and translation factors. However, it accumulates dramatically within the nucleus in response to various pathogenic and nonpathogenic stresses, leading to an inhibition of mRNA export. The molecular events th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
80
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 83 publications
6
80
0
1
Order By: Relevance
“…(89)(90)(91). Conversely, it is worth noting that NLS peptides have also been found to be masked in both cellular and viral protein contexts (85,(91)(92)(93). To our knowledge, this study is the first to directly implicate NES masking as a regulatory feature of Rev trafficking and the HIV-1 life cycle and may be relevant to previous observations from Daelemans and coworkers wherein targeted disruption of Rev multimerization caused reduced steady-state levels of Rev in the nucleolus (94,95).…”
Section: Discussionsupporting
confidence: 72%
“…(89)(90)(91). Conversely, it is worth noting that NLS peptides have also been found to be masked in both cellular and viral protein contexts (85,(91)(92)(93). To our knowledge, this study is the first to directly implicate NES masking as a regulatory feature of Rev trafficking and the HIV-1 life cycle and may be relevant to previous observations from Daelemans and coworkers wherein targeted disruption of Rev multimerization caused reduced steady-state levels of Rev in the nucleolus (94,95).…”
Section: Discussionsupporting
confidence: 72%
“…They propose a model in which poly(A) RNA binds PABP1, masking an NLS and thus preventing translocation into the nucleus. Conversely, when PABP1 is not bound by poly(A) RNA, it is translocation competent (63). It follows that, under normal conditions, when cytoplasmic levels of poly(A) RNA are relatively high, PABP1 remains predominantly cytoplasmic.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been hypothesized that a nontraditional nuclear localization sequence (NLS) resides within the RRM. Kumar et al demonstrated that the presence of poly(A) RNA antagonizes PABP1's ability to interact with nuclear import factors and a depletion of poly(A) RNA from the cytoplasm results in PABP1 relocalization to the nucleus (63). They propose a model in which poly(A) RNA binds PABP1, masking an NLS and thus preventing translocation into the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data implicate that the nuclear accumulation of PABPC is resulting from virus-induced mRNA depletion from the cytoplasm (32). Interestingly, cellular expression of PABPC is altered upon infection by members of all herpesvirus subfamilies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, interaction of PABPC with mRNAs retains PABPC in the cytoplasm (32). Upon expression of KSHV SOX and subsequent mRNA depletion from the cytoplasm, PABPC is relocalized to the nucleus (32,35), where it induces hyperadenylation and nuclear retention of Macacine herpesvirus 4 gi|24943119…”
mentioning
confidence: 99%